Stress and Stiffness Analysis of Geometric Design of Structure Universal Testing Machine 1 Ton Capacity With Ribbing Technology Using Finite Element Method - reski septiana; Hendra; Zuliantoni; Hamdan Akbar Notonegoro; Rispandi Rispandi; Hernadewita; Hermiyetti; Fajri A. Rayhan; M. Irfan Dzaky (Department of Mechanical Engineering, Universitas Andalas, 2026)
A machine structure is designed with a high stiffness concept [1]. Low stiffness leads to deformation of the machine structure, which can degrade the quality of the resulting product. High machine structural stiffness is used in machine tools, material testing machines, and other testing machines, such as universal testing machines. High machine structural stiffness is always accompanied by a large machine design volume, which requires the use of large amounts of material, resulting in high volume and weight and high production costs. To overcome this, ribbing technology is used [2-5]. Ribbing technology functions to prevent deformation in the machine structure while reducing the machine's volume. This study aims to apply and analyze the structural stiffness of a universal testing machine with various ribbing configurations using the finite element method [6-9]. The results show that the thicker the ribbing dimension, the smaller the resulting deflection, and the smaller the deflection, the greater the stiffness. The simulation results show that the highest deflection value was obtained for the 4 mm thick Box model using AISI 1010 material (1.55 mm), while the smallest was for the 16 mm thick X model using AISI 1045 material (1.26 mm). The lowest stiffness value was found for the 4 mm-thick Box model using AISI 1010 material (6472.49 N/mm), while the highest was found for the 16 mm-thick X model using AISI 1045 material (7936.51 N/mm).